PENDAMPINGAN PELAPORAN PAJAK BUMDES PADA DESA RANGKASBITUNG - Purwasih, Desy; Handayani, Asih; Anjilni, Ratih Qadarti (Publika Citra Media, 2025)
This Community Service (PKM) activity aims to Increase Knowledge by providing a deep understanding of the application of taxes on BUMDes and the benefits that can be obtained from its use, Develop Practical Skills, Increase Access and application of tax calculations on BUMDes Rangkasbitung Village. This activity will involve three lecturers from the Bachelor of Accounting Study Program, Faculty of Economics and Business, Pamulang University (UNPAM), who will provide intensive training and mentoring to the management of BUMDes Rangkasbitung Village. The method used in this activity is Group-based, comprehensive socialization, and digital technology-based. Furthermore, the above method is implemented in 4 (four) stages, namely: (1) Socialization, (2) competency improvement, (3) mentoring (4) monitoring and evaluation. The results of this monitoring and evaluation will be used as material for system improvements and adjustments, both from the technical side and from the operational side of BUMDes Rangkasbitung Village.